The Secret of Loyalty: Management Strategy and Citizen Behavior in Public Services - Welly, Surjono; Mersiana, Setiarini; Saepudin, .; Marnoto, . (INTI International University, 2025)
In an era of dynamic social and economic transformation, public institutions are increasingly expected not only to provide services but also to build long-term relationships based on public trust. This book emerges from an in-depth study on marketing strategy, customer behavior, satisfaction, and trust within the context of public service delivery. The author believes that management strategy in the public sector is no longer a mere administrative tool, but a strategic approach emphasizing the value of relationships, satisfaction, and user loyalty. This research bridges the gap between traditional management theory and public service management practice in Indonesia. Employing an empirical analysis using Structural Equation Modeling (SEM), the findings demonstrate that the implementation of management strategy and citizen behavior significantly influence satisfaction and trust, which in turn have strong implications for participant loyalty. This book is written to broaden academic and public understanding of the importance of trust and satisfaction in strengthening public service systems. Readers will be guided to see how modern management concepts such as customer relationship, trust-building, and service quality can be effectively applied in public institutions. Therefore, this work is expected to contribute both conceptually and practically to the development of a more human-centered, professional, and sustainable model of public service management. The author expresses sincere gratitude to Universitas Sangga Buana Bandung and all parties who have supported the completion of this research and publication. It is the author’s hope that this book serves as a valuable reference for scholars, policymakers, and practitioners committed to improving the quality of public services in Indonesia and across the ASEAN region.